Changes in Agricultural Markets in Poland following its Accession to the European Union - Czyżewski Andrzej; Czakowski Dariusz (Management)
This article attempts to determine the most significant tendencies and changes observed in Poland’s core markets of agricultural products, which occurred during the period preceding Poland’s accession to the European Union (1994-2003) and after the accession (2004-2013). The key markets of agricultural products include markets with the largest value of commodity production during the analysed period, such as cereals, potatoes, sugar beet, rapeseed, fruit, vegetables, pork, beef and poultry, cows’ milks and eggs. The development of domestic production, consumption and real purchasing prices were observed and compared in order to achieve the main objective. The research was preceded by the characterisation of macroeconomic and resource conditionalities of agricultural production as well as the trade balance of the Polish agri-food sector. On the basis of the conducted studies, there were singled out three groups of markets in which the situation during the period following Poland’s accession to the EU developed in a similar way.